2009
DOI: 10.1149/1.3095515
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Enhanced ALD of TiO[sub 2] Thin Films on SUS 304 Stainless Steel for Photocatalytic Application

Abstract: Plasma-enhanced atomic layer deposition ͑PE-ALD͒ of TiO 2 thin films using Ti͑NMe 2 ͒ 4 ͓tetrakis͑dimethylamido͒ Ti͔ and O 2 plasma were prepared on stainless steel to show the self-cleaning effect. The TiO 2 thin films deposited on stainless steel have high growth rate, large surface roughness, and low impurities. The film deposited below 200°C was amorphous, while the films deposited at 300 and 400°C showed anatase and rutile phases, respectively. The contact angle measurements on crystalline PE-ALD TiO 2 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…The films deposited at 50 and 150 o C showed 3.5 and 2% of carbon impurities [384]. Lee et al reported very high GPC values around 2 Å/cycle even around 100-200 o C, however neither the carbon content, nor pulse saturation was commented [747,749]. For the Ti(NMe2)4/H2O plasma process the GPC-vs.-temperature trend was very similar to that of the thermal process [384].…”
Section: Ti(nme2)4 With H2o H2o2 or O3mentioning
confidence: 79%
See 4 more Smart Citations
“…The films deposited at 50 and 150 o C showed 3.5 and 2% of carbon impurities [384]. Lee et al reported very high GPC values around 2 Å/cycle even around 100-200 o C, however neither the carbon content, nor pulse saturation was commented [747,749]. For the Ti(NMe2)4/H2O plasma process the GPC-vs.-temperature trend was very similar to that of the thermal process [384].…”
Section: Ti(nme2)4 With H2o H2o2 or O3mentioning
confidence: 79%
“…The poor crystallization tendency is not necessarily related to incomplete surface reactions and consequent high carbon and/or nitrogen content, as the films are reported to be of high purity [384,634,636]. Regarding the O2 plasma-based process, formation of the rutile structure was seen for films deposited on stainless steel substrates at 400 o C, while on silicon substrates mixed-phase anatase-rutile structure formed at 300 o C and above [746,747,749]. Xie et al compared H2O, H2O plasma and O2 plasma as the oxygen source for Ti(NMe2)4; the highest level of carbon impurities was found for the Ti(NMe2)4/O2 plasma process, which correlated with the poor crystallization tendency upon annealing [384].…”
Section: Crystal Structurementioning
confidence: 97%
See 3 more Smart Citations